Empowering through design: a case of becoming - Churchill, Lynn; Smith, Dianne; Lommerse, Marina (Curtin Uni, 2012)
Women who have been at-risk or are at-risk from being harmed by themselves or others may be fragile, disempowered, and at times invisible. To be at-risk relates to psychological, physical, social or cultural conditions that can cause instability, reduced faculties or lack of control in some way, all of which affect the sense of self. How we experience a sense of self often arises from our position within a particular social setting. Erving Goffman, who refers to ‘impressions’ or ‘performances’ that create an ‘image’ of self, writes that this experience of self ‘does not derive from its possessor, but from the whole scene of [her] action, being generated by that attribute of local events which renders them interpretable by witness. [T]he self — is a product of a scene.’ Often, when seeking help in an emergency or as a means of escape, victims of domestic violence find themselves in another ‘scene,’ a post-trauma, that will continue to mark them as victims or as powerless, and this can lead to a perpetuation of the cycle of crisis. This research seeks to mitigate such an outcome, to affect the kind of places in which women and children find themselves when they are fragile. Our intention is to begin by developing an understanding and a strategy to inform an effective and collaborative way of working with women who have experienced domestic violence. This non-traditional collaborative design process challenges existing widespread paradigms currently responsible for generating community and social infrastructure.Our research team draws from, among others, Christopher Day’s research into consensus design, and Ian Butterworth’s research into wellbeing and the built environment. We are inspired by designers such as Gordon Matta-Clark, who reacted against the temerity of urban design and architecture. A related installation, ‘Dis[place]ment: a woman’s perspective’, in the IDEA 2012 Exhibition An Interior Affair: a State of Becoming, communicates links between the idea of women’s place and experiences of vulnerability and safety. Together the will be used as a platform to launch a community project DURING 2013. The Symposium will host a workshop to explore the topic with those interested in this field, and to attract involvement in this project. Through the analysis of three national and international examples of participatory design practice, the definitions and efficacy of participatory, consultative, collaborative and democratic design are considered. Ultimately we aim to establish practices, which engages and empower those who are involved as uses, by involving them in the process of designing environments such as refuges.